Astaxanthin in Exercise Metabolism, Performance and Recovery: A Review - Brown, Daniel R.; Gough, Lewis A.; Deb, Sanjoy K.; Sparks, S. Andy; McNaughton, Lars R. (Frontiers in Nutrition, 2018)
During periods of heavy exercise training and competition, lipid, protein and nucleic molecules can become damaged due to an overproduction of reactive oxygen and nitrogen species within the exercising organism. As antioxidants can prevent and delay cellular oxidative damage through removing, deactivating and preventing the formation of reactive oxygen and nitrogen species, supplementation with exogenous antioxidant compounds has become a commercialised nutritional strategy commonly adopted by recreationally active individuals and athletes. The following review is written as a critical appraisal of the current literature surrounding astaxanthin and its potential application as a dietary supplement in exercising humans. Astaxanthin is a lipid-soluble antioxidant carotenoid available to supplement through the intake of Haematococcus pluvialis-derived antioxidant products. Based upon in vitro and in vivo research conducted in mice exercise models, evidence would suggest that astaxanthin supplementation could potentially improve indices of exercise metabolism, performance and recovery because of its potent antioxidant capacity. In exercising humans, however, these observations have yet to be consistently realised, with equivocal data reported. Implicated, in part, by the scarcity of well-controlled, scientifically rigorous research, future investigation is necessary to enable a more robust conclusion in regard to the efficacy of astaxanthin supplementation and its potential role in substrate utilisation, endurance performance and acute recovery in exercising humans.